Research on the evaluation and spatial layout of high quality development of higher education in China - Wen Li; Jinfa Shi; Qiting Zuo; Jianqin Ma; Meng Qiu; Yushun Zhang (PLoS ONE, 2026)
As a social subsystem, the layout of higher education is related to the degree of harmony in the economy and society. Based on the panel data from the “China Statistical Yearbook”, “China Education Statistical Yearbook” and the “Education Statistical Yearbook” of China’s provincial administrative regions from 2000 to 2022, considering factors such as sustainable economic and social development capacity, regional scientific and technological cultural development level, and spatial layout of higher education, this study determines the degree of harmonic development among the three subsystems. This paper constructs an indicator system for harmonious development of China’s higher education, and uses the method of “single indicator quantification-multi indicator synthesis-multi criteria integration” (SMI-P) to determine the harmonious development index of China’s higher education. The ArcGIS spatial analysis method is used to study the spatial distribution changes of higher education harmonious development in China’s 31 provincial administrative regions. Then, the Tobit model is used to analyze the impact of various economic and social factors, scientific and cultural factors or layout of higher education factors on the harmonious development of higher education, in order to optimize the spatial layout of China’s higher education resources, balance education development, narrow regional disparities, promote regional coordination, and enhance the overall competitiveness of higher education. Research has found that: (1) The development of higher education subsystems shows a trend of convergence; (2) Over the past 23 years (from 2000 to 2023), the spatial centroid of harmonious development of higher education (HDHE) in China shifted southward; (3) There is a strong spatial interaction between 3 subsystems of harmonious development of higher education in China(economic society subsystem, technology and culture subsystem, and higher education subsystem); (4) The main factors affecting HDHE in China include the degree of regional ecological civilization, the ratio of university students to teachers and the per capita domestic patent application authorization.